Nagari Government Cooperation with Nomads Monitors in the Development of Nagari Sulit Air District of Solok - Ridho Yoliandri; Hendri Koeswara; Syamsurizaldi Syamsurizaldi (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2022)
Nomads in West Sumatra have a very big share in the development of the village, one of which is Sulit Air, which has quite a several Nomads and has a nomadic organization called Sulit Air Sepakat (SAS) so that it becomes one of the overseas assisted villages that must collaborate with nomads in the social, cultural and economic fields. It turns out that the implementation of cooperation has not yet been realized. There are problems such as coordination between parties collaborating with local governments and commitments from collaborating parties the purpose of this research is to describe the implementation of cooperation between the Nagari government and migrants in the development of Nagari Sulit Air in Solok Regency. This research uses the descriptive qualitative method. Data collection techniques using interviews and documentation. The result shows that the implementation of the cooperation has not been implemented as a whole. In the initiation process, the collaboration has been carried out well, starting from the beginning of the collaboration to the actors involved and the relationships between actors. Areas of cooperation are also carried out well with the submission of work plans but the areas that are cooperated have not been developed. There is nobody for organizing cooperation that is authorized to carry out this cooperation. The responsibility of the cooperation parties is still high but the commitment between the parties is reduced, one of which is due to the difficulty in resolving land acquisition problems.